A new model for thoracic radiology teaching and research in cadavers of embalmed dogs - Kihara, Mariana Tiai [UNESP]; Zero, Rafael Chiarelo [UNESP]; De Souza Queiroz, Andréa Barros Piazzon [UNESP]; Toscano, Cauê Pereira; Jarrouge, Daniel Herreira; De Sá Rocha, Thiago André Salvitti; De Oliveira, Fabrício Singaretti [UNESP] (FapUNIFESP (SciELO), 2024)
Nowadays, alternative methods that do not use formaldehyde to preserve cadavers must be used due to this substance’s toxicity. Synthetic models are a training option for teaching, but cost makes their use unviable in most underdeveloped countries. The present study’s main objective was to develop a model for education and researching thorax radiology in cadavers of chemically prepared dogs. Megaesophagus, pleural effusion, pneumothorax, and bronchography, as well as pulmonary insufflation, were simulated in 32 dogs cadavers, which received 150 mL/kg of pure ethyl alcohol solution with 5% glycerin followed by injection of 120 mL/kg of a solution containing 20% sodium chloride, 1% sodium nitrite and 1% sodium nitrate; they were kept refrigerated between 2 to 6 °C, for 30, 60, 90 or 120 days (G30, G60, G90, G120). There was no contamination, putrid odor, or subcutaneous emphysema. The pulmonary insufflation was kept, and the color and the consistency were similar to a fresh corpse after 120 days of conservation. It was possible to perform radiographic procedures, and almost all affections could be greatly mimicked. Megaesophagus and bronchography were easily simulated. Pneumothorax was the most challenging condition to be reproduced, especially in cadavers with some liquid in the thorax. The alcoholic and curing salt solutions are an embalming alternative with low financial and environmental costs and proved to preserve corpses.
Um novo modelo visando ao ensino e pesquisa da radiologia torácica em cadáveres de cães quimicamente preparados
Keywords: Anatomy; Preservative solutions; Radiography; Training